The Effect of Participation in Pregnant Women's Class on The Time Range of Contraception Use in The Minasatene Public Health Center - Hasriani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
The usage of contraception is a problem that leads to maternal mortality. According to the 2012 IDHS, the rate of unmet demand is 8.5%. The significant unmet need for family planning services increases the likelihood of unwanted pregnancies (UP). If UP is prolonged in postpartum women, it will result in a very close pregnancy distance, and there is a risk of abortion difficulties if it is interrupted. Pangkep Regency has the fewest new and active family planning participants in South Sulawesi Province, with the lowest percentages in the Minasatene Health Center, at 62.04% and 76.73%, respectively. Meanwhile, the class program for pregnant women has been implemented in all Public Health Center in Pangkep Regency, including one at the Minasatene Health Center, in compliance with the rules for conducting courses for pregnant women. The goal of this study was to see how participation in the Pregnant Women's Class (PWC) affected the time span of contraceptive usage. This is an analytic observational study with a cross-sectional design with 73 respondents recruited by purposive sampling and the Simple Linear Regression Test. From 73 respondents, it is known that the majority of participation in the class of pregnant women is not in accordance with the standards, namely as many as 57 mothers (78.08%) and the time span of using contraception that is not according to standards (> 42 days) as many as 20 mothers (27.39%). The results of the analysis test of the Simple Linear Regression Test obtained the value of p = 0.004 (p = <0.05). The study concludes that participation in the Pregnant Women Class (PWC) has an influence on the duration span of contraceptive usage at the Minasatene Health Center, Pangkajene and Islands Districts in 2022.